The effects of chronic subcutaneous exposure to low dose of chlorpyrifos on the rat kidneys - Aung, Sanda (Kulliyyah of Medicine, International Islamic University Malaysia, 2020)
Introduction: Chlorpyrifos (CPF) is an organophosphate (OP) that is widely used as pesticide in agriculture. Epidemiological studies reported that the incidence of chronic kidney disease (CKD) of unknown cause was increasing among agricultural workers who were exposed to OPs during their working life through dermal contact. However, there is little information on the effects of chronic subcutaneous low dose of OP CPF on kidney in experimental animals. To date, the mechanism of OP-induced kidney damage is not fully elucidated. Objective: The aim of this study was to assess the effects of chronic subcutaneous low dose of OP CPF exposure on the kidney by investigating the structure and function of kidney and to assess the possible mechanisms of OP-induced kidney damage. Methodology: Eighteen male Sprague Dawley rats were randomly divided into three groups, with six rats in each group. Group 1 served as control group, while groups 2 and 3 received subcutaneous vehicle (3% dimethyl sulfoxide + 97% v/v soy oil) and CPF (18.0 mg/kg) respectively, every other day for 180 days. Blood was taken for biochemical analysis while kidney tissues were harvested for histology, immunohistochemistry (IHC) and selective gene expression. Cystatin C, acetylcholinesterase (AChE), advanced glycation end products (AGEs) and malondialdehyde (MDA) levels were measured using quantitative sandwich enzyme immunoassay. Results: Biochemical parameters (urea, creatinine, uric acid, glucose), cystatin C, AGEs and MDA levels were significantly increased (p < 0.05), while AChE activity and electrolytes levels were significantly decreased (p < 0.05) in the CPF-exposed rats. Structural damage of kidney, including diffuse global glomerular hypercellularity and diffuse necrosis of proximal tubular cells were observed in CPF-exposed kidney. IHC revealed strong immunostaining of polyclonal anti-AGEs in glomeruli and polyclonal anti-MDA in the proximal tubular cells of CPF-exposed rats. The expression of genes involved in glucose metabolism (Ager), oxidative stress (Sod3, Cat, Gsr, Pon1 and Nos2) and cell death pathways (Cycs, Casp3, Casp, 8, Casp, 9, Ripk1, Ripk3, Cst3, Havcr1 and Lcn2) showed downregulation trend. Conclusion: Chronic subcutaneous low dose of CPF caused renal dysfunction as evidence by increased endogenous glomerular filtration markers and reduced electrolytes levels and structural kidney damage. The downregulation of these genes could be due to selective exhaustion of pathways that were persistently activated during the prolonged chronic OP-mediated injury. In brief, chronic subcutaneous low dose of CPF caused nephrotoxicity. The process could be facilitated by the effects of CPF on glucose metabolism and oxidative stress.